PENGARUH KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR (STUDI KASUS PADA KANTOR SAMSAT GARUT) - Putri , Neng; Rachman , Fatwa Rubiar; Christian , Ivan (Publika Citra Media, 2024)
This research aims to determine the influence of taxpayer awareness and compliance in paying motor vehicle tax at the Garut Samsat Office. This research uses quantitative methods. The population in this study was 168,636 taxpayers at the Garut Samsat Office. The sampling technique used was simple random sampling, so a sample size of 100 taxpayers was obtained. The type of data for this research is primary data obtained through a questionnaire. The data analysis technique used is simple linear regression analysis and hypothesis testing. Hypothesis testing is carried out using the t test. Data processing uses the SPSS 24 application. The research results show that taxpayer awareness has a positive and significant effect on motor vehicle taxpayer compliance.